2009
DOI: 10.1007/s10562-009-0091-z
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Calcination Temperature on the Catalytic Performance of γ-Bi2MoO6 in the Oxidative Dehydrogenation of n-Butene to 1,3-Butadiene

Abstract: c-Bi 2 MoO 6 catalysts prepared by a co-precipitation method were calcined at various temperatures (425-675°C), and were applied to the oxidative dehydrogenation of n-butene to 1,3-butadiene in a continuous flow fixed-bed reactor. Conversion of n-butene and yield for 1,3-butadiene were high at low calcination temperature (425-475°C), but were decreased with increasing calcination temperature (525-675°C). Temperature-programmed reoxidation (TPRO) measurements revealed that the catalytic performance of c-Bi 2 Mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Moreover, the peak area of O 2 -consumption on Bi 2 MoO 6 -S was 1.4 times higher than that on Bi 2 MoO 6 -F. The O 2 -consumption behaviour generally indicates the reactivity of oxygen species on Bi 2 MoO 6 samples, which was intimately correlated with the catalytic activities for the selective oxidation of isobutene. 48,50 The lower the temperature, the higher the oxygen mobility. Therefore, the TPRO test solidly demonstrated that the Bi 2 MoO 6 -S catalyst presents a higher oxygen mobility than Bi 2 MoO 6 -F, which subsequently improved the catalytic performances for the oxidation of isobutene.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the peak area of O 2 -consumption on Bi 2 MoO 6 -S was 1.4 times higher than that on Bi 2 MoO 6 -F. The O 2 -consumption behaviour generally indicates the reactivity of oxygen species on Bi 2 MoO 6 samples, which was intimately correlated with the catalytic activities for the selective oxidation of isobutene. 48,50 The lower the temperature, the higher the oxygen mobility. Therefore, the TPRO test solidly demonstrated that the Bi 2 MoO 6 -S catalyst presents a higher oxygen mobility than Bi 2 MoO 6 -F, which subsequently improved the catalytic performances for the oxidation of isobutene.…”
Section: Resultsmentioning
confidence: 99%
“…Originally, the Bi 2 MoO 6 nanoparticles were synthesized by the solid‐state reaction (SSR) and co‐precipitation technology . In a solid‐state reaction, some groups have employed Bi 2 O 3 and MoO 3 as the precursor materials with different ratio of Bi/Mo to obtain Bi 2 MoO 6 with good crystal structure .…”
Section: Modulated Strategies Of Bi2moo6‐based Materials With Multifumentioning
confidence: 99%
“…Although other methods (spray drying, solution combustion, ultrasonic‐assisted synthesis, sol–gel method, and so on) were developed to regulate and control the size, morphology and phase of Bi 2 MoO 6 particles, the necessary calcination process strongly influenced the phase transformation and the surface area. As known, the size of particles grows as the calcination temperature increases, accompanying by the shrink of surface area, while the γ‐Bi 2 MoO 6 is generally obtained at more than 425 °C . Therefore, to overcome these drawbacks encountered in the Bi 2 MoO 6 particles, new morphologies and structures need to be studied by shifting the chemical synthesis conditions.…”
Section: Modulated Strategies Of Bi2moo6‐based Materials With Multifumentioning
confidence: 99%
“…[ 70–72 ] During the last decade, tremendous efforts have been devoted to optimizing the photocatalytic activity of Bi 2 MoO 6 through nanostructure regulation. Thus, various approaches have been explored to synthesize Bi 2 MoO 6 ‐based nanostructures, such as solid‐state reaction, [ 73,74 ] coprecipitation technology, [ 75,76 ] electrostatic spinning, [ 77,78 ] and hydro(solvo)thermal treatment. [ 79,80 ] Among them, hydro(solvo)thermal treatment has aroused much attention, as it not only owns the merit of simple handling and low overhead, but also can effectively optimize the sizes, morphologies, and even exposed facets of catalysts through adjusting the reaction parameters, including solution composition, reaction time and temperature, and additional surfactants.…”
Section: Typical Strategiesmentioning
confidence: 99%